Tribological Analysis of Mg2Si Particulates Reinforced Powder Metallurgy Magnesium Alloy Composites under Oil Lubrication Condition - Katsuyoshi Kondoh; Junko Umeda; Kenshi Kawabata (Advances in Materials Science and Engineering)
For the evaluation of wear behavior of Mg composites under oil lubrication conditions, powder metallurgy Mg97Y2Zn1 alloy reinforced with additive Mg2Si particles were fabricated by the repeated plastic working (RPW) and hot extrusion. The RPW process was effective in refining both Mg2Si reinforcements and α-Mg grains causing the matrix hardening. When increasing the repetition number of RPW process from 200 to 600 cycles, the particle size of Mg2Si additives changed from 8 μm to 1~2 μm, and α-Mg grain size was 1 μm or less. With regard to the defensive and offensive properties of Mg alloys reinforced with Mg2Si dispersoids, the composite had superior adhesive wear resistance compared with the conventional Mg alloys because of its extremely high microhardness of 95~180 Hv by RPW process. The uniform distribution of refined Mg2Si particles was useful for improving both defensive and offensive properties against AZ31B counter disk specimens. The Mg2Si prominent dispersoids in the matrix were also effective in forming the oil grooves around them, and caused the low and stable friction coefficient. On the other hand, in the case of the composite containing coarse Mg2Si particles, severely deep scratches were given on the counter face of the AZ31B disk, and resulted in an unstable and high friction coefficient.